A small molecule II-6s inhibits Enterococcus faecalis biofilms. Issue 1 (1st January 2021) - Kuang, Xinyi; Zhang, Jin; Peng, Xian; Xie, Qian; Li, Jiyao; Zhou, Xuedong; Luo, Youfu; Xu, Xin
ABSTRACT: Background: Limitations of current intracanal irrigants such as sodium hypochlorite (NaOCl) and chlorhexidine (CHX) necessitate the development of novel antimicrobial agents to control endodontic infection. Aim: This study investigated the antimicrobial activities of a small molecule II-6s against Enterococcus faecalis associated with endodontic diseases. Methods: The susceptibility of E. faecalis to II-6s was evaluated by the microdilution method and time-kill assay. Microbial resistance was assessed by repeated exposure of E. faecalis to II-6s. Cytotoxicity of II-6s was evaluated by CCK-8 assay. Virulence gene expression of the II-6s-treated E. faecalis cells was measured by RT-qPCR. Bacterial reductions in the dentinal tubules were further assessed by confocal laser scanning microscopy. Results: II-6s exhibited potent antimicrobial activity against E. faecalis and down-regulated virulence-associated genes in E. faecalis . II-6s induced no drug resistance in E. faecalis with lower cytotoxicity as compared to NaOCl and CHX. More importantly, 0.003125% II-6s exhibited significant bactericidal effect against E. faecalis residing in the dentinal tubules, which was comparable to 5.25% NaOCl and 2% CHX. Conclusions: II-6s has excellent antimicrobial activity, moderate cytotoxicity and induces no drug resistance, and thus is a promising agent for the treatment of endodontic infection.